RhoA/ROCK-1 Signaling Pathway and Oxidative Stress in Coronary Artery Disease Patients - Dokumacioglu,Eda (2022)
Abstract Introduction: Coronary artery disease (CAD) is an ischemic condition that occurs as a result of partial or complete interruption of blood flow by narrowing or complete blockage of the vessels supplying the heart, which are called coronary arteries. Our objective in this study is to investigate the RhoA/Rho-associated kinase (ROCK)-1 signaling pathway and oxidative stress in CAD patients. Methods: A total of 81 individuals aged between 40-70 years - including 45 patients (15 females and 30 males) who were admitted to the Artvin State Hospital Cardiovascular Surgery Clinic and were diagnosed with CAD and 36 healthy volunteers (15 females and 21 males) - participated in this study. Serum samples were tested for total cholesterol, triglyceride, low-density lipoprotein, high-density lipoprotein, malondialdehyde (MDA), superoxide dismutase (SOD), RhoA, and ROCK-1 values. Results: Serum RhoA, MDA levels, and ROCK-1 activity in the CAD group were found to be statistically significantly higher than in the control group (P<0.001). Concordantly, serum SOD activity was found to be statistically significantly lower in the CAD group than in the control group (P<0.001). Conclusion: Inhibition of the activity of RhoA/ROCK-1 pathway would be beneficial in treating cardiovascular diseases since this pathway plays an important role in the development of these diseases.